2016
DOI: 10.14740/jem326w
|View full text |Cite
|
Sign up to set email alerts
|

Inaccuracies of Hemoglobin A1c in Liver Cirrhosis: A Case Report

Abstract: Hemoglobin A1c (HbA1c) is the gold standard for the measurement of long-range glycemic control in patients with diabetes mellitus type 2 (T2DM). In a rare subset of patients, this measurement may not be reliable. Inaccuracies of HbA1c in liver cirrhosis are rare, but documented. The objective of this study was to increase awareness about low HbA1c in liver cirrhosis and discuss alternative biomarkers that can be used to measure glycemic control. We present the case of a 61-year-old Caucasian female, with histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 5 publications
3
3
0
Order By: Relevance
“…In this study, HbA1c was found to be insufficient marker when used alone, a discovery in agreement with a case report by Clarke et al 30 suggesting that possible interference with HbA1c stability and accuracy may be explained by the array of different factors commonly seen in hepatic patients. These include shortened RBC life span, anemia induced by or associated with cirrhosis (anemia of chronic disease), in addition to diminished albumin level, gastrointestinal bleeding, and hypersplenism causing sequestration of RBCs all contributing to such a decreased HbA1c concentration that it no longer has any significance in determining hepatic fibrosis or assessing its grade 30 . In fact, values of HbA1c become so low in these patients that it even becomes ineffective in monitoring the glycemic state 31 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this study, HbA1c was found to be insufficient marker when used alone, a discovery in agreement with a case report by Clarke et al 30 suggesting that possible interference with HbA1c stability and accuracy may be explained by the array of different factors commonly seen in hepatic patients. These include shortened RBC life span, anemia induced by or associated with cirrhosis (anemia of chronic disease), in addition to diminished albumin level, gastrointestinal bleeding, and hypersplenism causing sequestration of RBCs all contributing to such a decreased HbA1c concentration that it no longer has any significance in determining hepatic fibrosis or assessing its grade 30 . In fact, values of HbA1c become so low in these patients that it even becomes ineffective in monitoring the glycemic state 31 …”
Section: Discussionsupporting
confidence: 92%
“…To assess the diagnostic value of various glycated compounds in hepatic fibrosis, levels of GA and HbA1c were measured and the GA/HbA1c ratio was calculated. In this study, HbA1c was found to be insufficient marker when used alone, a discovery in agreement with a case report by Clarke et al 30 concentration that it no longer has any significance in determining hepatic fibrosis or assessing its grade. 30 In fact, values of HbA1c become so low in these patients that it even becomes ineffective in monitoring the glycemic state.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…HbA1c although considered to be a good marker of glucose control, may be falsely low in cirrhotics. [21][22][23][24] Laboratory parameter like low serum albumin which is considered specific in patients with cirrhosis, was found to be present only in 54.1% of the cirrhotic patients indicating its low sensitivity as a marker of cirrhosis. Ascites was the most common clinical finding, followed by hepatic encephalopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Achievement of optimal blood glucose control in patients awaiting liver transplantation is challenging because the metabolic and hematologic derangements associated with advanced liver disease reduce the reliability of the most commonly employed long‐term measures of glycemia, including HbA1C, fructosamine, and glycated albumin (GA) . To address this problem, Koga et al formulated a chronic liver disease A1C (CLD‐A1C) comprising the average of HbA1C and GA/3.…”
Section: Discussionmentioning
confidence: 99%